ANALISIS FAKTOR PENENTU PRICE EARNINGS RATIO: STUDI PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yaqin, Maulana Ainul; Imamah, Nur (Profit: Jurnal Adminsitrasi Bisnis, 2021)
This study aims to determine the effect of the Dividend Payout Ratio, Earnings Growth Ratio, Debt to Asset Ratio, and Dividend Per Share on the Price Earnings Ratio of companies listed on the LQ45 Index in the Indonesian capital market for the 2016-2018 period. This study is an explanatory research. Analysis of the data used is multiple linear regression analysis with Ordinary Least Squares (OLS) approach. The results showed that the Dividend Payout Ratio and Dividend Per Share had a significant effect on the Price Earnings Ratio. Meanwhile, Earnings Growth Ratio and Debt to Asset Ratio have no significant effect on Price Earnings Ratio. In addition, an interesting finding in this study is that the Dividend Payout Ratio is the most dominant ratio in determining the Price Earnings Ratio. The results also show that the coefficient of determination (R2) is 73.6%. This explains that the ratios used in this study are important to determine or influence the value of the Price Earnings Ratio.Â